The Constitutionalism of the Americas - Mendívil, José (2021)
With the purpose to solve recurring problems about governability of the peruvian Republic corroded by mediocrity and corruption, and in order that the long-standing exclusion from the life of the nation of part the Peruvians who trace their origins to Caral and to the Tahuantinsuyo and having started 'ethnic revolutions' in defense of their territories and rights, in this essay I proposes to spend the constitutionalism of the legislature as a mechanism to reform the 1993 constitution, the ataráxico constitutionalism that gives stability to the republic and pro: mote consensual constitutional reforms to prevens us from falling in to similar couse to that the followed villages Bolivia and Ecuador to approve his recent constitutions; and we can move forward with prudence and certainty toward a truly pluralistic society and an effectively sovereign state.